KEDUDUKAN PERATURAN DESA DALAM SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Nirwan Moh. Nur; Firmansyah Fality (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2020)
The existence of village regulations is very important in the implementation of village government. So in this article want to analyze the position of village regulations based on the prevailing system of laws and regulations. The research method used in the framework of this writing is normative legal research. Thus it is obtained that the position of village regulations based on the legal system in Indonesia, can be reviewed based on 2 (two) laws that have been and are in force. It is affirmed that the position of village regulations is in the group of Laws and Regulations established by State Institutions such as MPR, DPR, DPD, MA, and so on. As a regulation established and mutually agreed between the Village Head and the Village Regulation Agency, the position of the village regulation should be seen as a legal product that does not mean regelling but is also placed as a product of legislation because its formation involves the community / people through its representatives in the institution of the Village Permusyawaratan Agency.